We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
142
1
avatar+701 

http://prntscr.com/lh3wt9

 Nov 11, 2018
 #1
avatar+101399 
+2

sqrt ( p + a)  + r  = k       subtract r from both sides

 

sqrt ( p + a)  =  k  - r      square both sides

 

p + a  =  ( k - r)^2

 

p + a  =  k^2 - 2kr + r^2      subtract p from both sides

 

a  =  k^2  - 2kr   + r^2  - p

 

 

cool cool cool

 Nov 11, 2018

10 Online Users

avatar